Production Performance of Dual Purpose Crosses of Two Indigenous with Two Exotic Chicken Breeds in Sub-tropical Environment - Bekele, Fassill; Adnoy, T.; Gjoen, H.M.; Kathle, J.; Abebe, Girma (International Journal of Poultry Science, 2010)
An ongoing crossbreeding experiment is being conducted with the objective of producing dual purpose synthetic chicken for village poultry production in Ethiopia. The two exotic chicken breeds used were the Fayoumi (F) and Rhode Island Red (R) as dam line, whereas the two indigenous chicken breeds used were the Naked neck (N) and local Netch (W); a white feathered chicken. The indigenous breeds were used as sire line to produce the hybrids FN (F♀ X N♂) and RW (R♀ X W♂). Growth and egg production performance of the crosses were compared with each other and with the exotic pure line performance. Both body and egg weight of FN was improved while body weight of RW was reduced and age at first egg was significantly reduced, compared to their respective dam line. Egg production for the crosses was lower than for their maternal lines. Although FN cross chicks weighed more and grew faster than RW chicks during the brooding period, the difference became insignificant as they grew older. However, the higher overall average body weight gain of RW crosses that was observed was mainly due to higher weight gain for the RW cocks. No significant differences were observed in overall egg production and quality traits between the two crosses, but significant age effect within crosses was found. Mortality in the FN cross was lower than in the RW cross. These F1 crosses will be used as parents to produce a 4-way synthetic crossbred chicken.